Olah Raga Mempengaruhi Tingkat Kewaspadaan Supir Dump Truck Shift Malam Kontraktor Tambang Batubara. - Simanjuntak, Johannes P H; Widjasena, Baju (Jurnal Promosi Kesehatan Indonesia, 2013)
This research use â€œComparative Cross Sectionalâ€Â  by observing 90 drivers as respondences. The data is taken by giving questioner and by doing Timer Reaction Time when they do their job at 01.00 am â€“ 05.00am. Based on the research, the affecting factors of the vigilance on the night shiftdump truck driver coal mining contractor at PT. AAA South Kalimantan are: 61% of the driver has a good vigilance level and 39% of the driver has a low vigilance level. The habbit such as drinking coffe, sleeping pattern, sleeping quality, and doing excercise has the most effect to vigilance level. The factors which have no relation to vigilance level are: age, education level, tenure, training status, marital status, the number of children, the age of the oldest child, other side job, smoking habbit, sleep duration,Â  stressing in job, and drugs consumption. The most affecting factor in the vigilance level is excercise. Based on the data on OR (Exp B) is 2,801 showing that the driver who do the excercise has 2.8 times than the driver who has no excercise. This reseach shows that the night shift dump truck driver coal mining contractor should do excercise minimally one week with 30 â€“ 60 minutes in duration. The company where they work should do stretching before doing excercise and Safety Talk.